2019
DOI: 10.29265/gypp.v28i1.545
|View full text |Cite
|
Sign up to set email alerts
|

La tarificación vial en el marco de las políticas de transporte urbano. Un estudio empírico sobre su aceptabilidad social y eficacia en la ciudad de Madrid

Abstract: La tarificación vial en el marco de las políticas de transporte urbano Un estudio empírico sobre su aceptabilidad social y eficacia en la ciudad de Madrid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…So, for such people, it will be cheaper to pay the PMT fare than to use their vehicle. Miguel and Rodriguez (2019) interviewed around 1,300 residents of Madrid (Spain), to learn how the population would behave if an urban toll was implemented in the city center. The survey showed that 25% of motorists would migrate to sustainable modes (PMT, walking or cycling), 18% would pay the toll to be able to continue using the car, 30% would change their route or timing to escape the charge, 11% would not be affected (they don't frequent the area where the charge would be levied) and 17% would be entitled to some kind of exemption (e.g.…”
Section: Government Electoral Gains Due To Lower Bus Faresmentioning
confidence: 99%
“…So, for such people, it will be cheaper to pay the PMT fare than to use their vehicle. Miguel and Rodriguez (2019) interviewed around 1,300 residents of Madrid (Spain), to learn how the population would behave if an urban toll was implemented in the city center. The survey showed that 25% of motorists would migrate to sustainable modes (PMT, walking or cycling), 18% would pay the toll to be able to continue using the car, 30% would change their route or timing to escape the charge, 11% would not be affected (they don't frequent the area where the charge would be levied) and 17% would be entitled to some kind of exemption (e.g.…”
Section: Government Electoral Gains Due To Lower Bus Faresmentioning
confidence: 99%
“…The fairness of establishing traffic tolls in the urban environment has been investigated by many authors, includingRichardson (1974);Izquierdo & Vassallo (2001);Villegas (2001);Ferrari (2005); Franklin (2007);Schweitzer & Taylor (2008);Zhicai, Qingyu, Zhongning & Hongfei (2008);Lauridsen (2011); Ortega Hortelano (2014); MuñozMiguel & Anguita Rodríguez (2019);Santos & Caranzo (2022).…”
mentioning
confidence: 99%